2011
DOI: 10.1371/journal.pone.0022903
|View full text |Cite
|
Sign up to set email alerts
|

Does Landscape Fragmentation Influence Sex Ratio of Dioecious Plants? A Case Study of Pistacia chinensis in the Thousand-Island Lake Region of China

Abstract: The Thousand-Island Lake region in Zhejiang Province, China is a highly fragmented landscape with a clear point-in-time of fragmentation as a result of flooding to form the reservoir. Islands in the artificial lake were surveyed to examine how population sex ratio of a dioecious plant specie Pistacia chinensis B. was affected by landscape fragmentation. A natural population on the mainland near the lake was also surveyed for comparison. Population size, sex ratio and diameter at breast height (DBH) of individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 55 publications
(61 reference statements)
0
28
0
2
Order By: Relevance
“…Characteristics of breeding systems, for example, the degree of protandry, self-incompatibility or sex ratios, might be affected by fragmentation Jennersten (1988), Yu and Lu (2011) Growth form Specific growth forms (e.g. clonal plants) might be more strongly affected than others (e.g.…”
Section: Dispersal Abilitymentioning
confidence: 99%
“…Characteristics of breeding systems, for example, the degree of protandry, self-incompatibility or sex ratios, might be affected by fragmentation Jennersten (1988), Yu and Lu (2011) Growth form Specific growth forms (e.g. clonal plants) might be more strongly affected than others (e.g.…”
Section: Dispersal Abilitymentioning
confidence: 99%
“…Unfortunately, we could not estimate fruit production in some of the smaller populations. Yu & Lu (2011) found that small populations of the dioecious Pistacia chinensis had a male-biased sex ratio, compared with larger, nonfragmented populations. They found that male-biased populations were established in soils with low nitrogen availability and they concluded that fragmentation affects soil nitrogen conditions at the microhabitat scale.…”
Section: Sex Ratio In Fuchsia Parvifloramentioning
confidence: 93%
“…The fact that sex ratio did not vary along the flowering season gives us more confidence on our sex ratio estimations. Few studies have reported the effect of population size on sex ratios (Soldaat et al 1997, Somanathan & Borges 2000, Yu & Lu 2011. If most individuals in a small population are males this may reduce the chances of fruit production and therefore the viability of populations.…”
Section: Sex Ratio In Fuchsia Parvifloramentioning
confidence: 99%
See 1 more Smart Citation
“…The sex ratio is affected at germination by sex-linked genes (Shelton 2010), pollination intensity (Field et al 2012) and soil nitrogen (Yu & Lu 2011). Sex ratios are affected by other factors as well, e.g., sexually different mortality rates (Stehlik & Barrett 2005).…”
Section: Inter-annual Trade-off At Different Modular Levelsmentioning
confidence: 99%